Integrated subsidiarity of the BCC-CR: a sustainable model of local finance - Sandro Turina; Giuseppe Confessore; Maurizio Turina (European Regional Science Association (ERSA), 2014)
In more than 130 years, the cooperative banks and rural banks, have become a best practice, widespread in all the Italian regions so as to become, through Federcasse, a federal system included among the 130 European banks, referents ECB. A model that today has about 400 local banks and that, discounting the guiding principles, interprets the function as a development bank for the area, responding to the economic and social needs of individual communities. Objective of a BCC-CR is, in fact, promote development from the bottom, making the protagonists subjects of the local economy through a process that is defined of circular subsidiarity because element of synthesis between the vertical subsidiarity (integration of the different levels expressed by territory) and horizontal subsidiarity (integration of factors of the local development). In order to analyze and deepen the best practice of the BCC -CR model is, therefore, interesting assess the sustainability of local finance through a relation of functionality that interconnects the level of performance expressed by some important national areas with the intensity of mission of the financial model. The research team has already developed a unique indicator of territorial performance, presented in the session ERSA, 2011 (Spain) and an indicator of intensity of the mission of the BCC -CR model presented in the Workshop RSAI 2012 (China) and in the annual conference PRSCO 2013 (Indonesia). This dimension of the subsidiarity has allowed the research team of assess the relative effectiveness of the model through the measurement of the level of integration between the horizontal subsidiarity and the vertical one by means the structuring of a function of two variables, that, represented by a spherical model in three-dimensional environment (the circular subsidiarity is expressed by level lines to shape of circumferences in two-dimensional level), expresses the intensity of the integration as a factor in the sustainability of local finance. Territorial cohesion and consistency with the orientations set by the different levels of governance is, in fact, a factor of local development able express the potentialities of the territory, the level of competitiveness and the ability to give concrete answers to the current critical issues. The study shows that there is room for improvement among the descriptors that express the intensity of the mission model BCC-CR (horizontal subsidiarity) and those that express the performance of the territory (vertical subsidiarity): on these areas should focus the attention of policy makers and the company management to improve the synchronization between demand of investment and the supply of savings in the territory.
Keywords: G21; G29; 330; Financial Institution; Financial Market; Financial Service